2006
DOI: 10.2174/138161206775201893
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Multidrug Resistance of Cancer Cells by Natural Diterpenes, Triterpenes and Carotenoids

Abstract: The multidrug resistance (MDR) proteins are member of the ATP-binding cassette superfamily and are present in a majority of human tumors. Their activity is a crucial factor leading to therapeutic failure. It is likely that compounds which inhibit the function of the MDR-efflux proteins such as MDR1 will improve the cytotoxic action of anticancer chemotherapy. Therefore, a search for MDR reversing compounds was conducted among three classes of plant derived compounds such as diterpenes, triterpenes and caroteno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…This is especially true if a patient is relapsing after a chemotherapy treatment because the remaining cancer cells are being selected for resistance, generally due to the increased expression of the ABC transporters [49]. Many pharmaceutical ABC transporter inhibitors are able to decrease drug efflux from cancer cells in vitro, but most tend to have serious and deleterious side effects in vivo, and none is currently approved for inclusion into chemotherapy treatments [19].…”
Section: Modulation Of Gut Mao Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true if a patient is relapsing after a chemotherapy treatment because the remaining cancer cells are being selected for resistance, generally due to the increased expression of the ABC transporters [49]. Many pharmaceutical ABC transporter inhibitors are able to decrease drug efflux from cancer cells in vitro, but most tend to have serious and deleterious side effects in vivo, and none is currently approved for inclusion into chemotherapy treatments [19].…”
Section: Modulation Of Gut Mao Enzymesmentioning
confidence: 99%
“…Treatment with SJW is able to reduce plasma levels of these drugs by up to 57% in healthy human volunteers, which could potentially lead to subtherapeutic levels and selective pressure for the creation of resistant viral particles in AIDS patients [62]. Recent work by Molnar et al [49] has shown that a wide range of naturally occurring lipophilic phytochemicals (diterpenes, triterpines and carotenoids) were able to inhibit human Pgp in vitro at the low lg/ml range, whereas other combinations had positive synergistic activity. Using purified polyphenols on Pgp overexpressing cells in vitro, Patel et al [59] showed that quercetin, hypericin and kaempferol were able to increase the cellular uptake of ritonavir by five-to eightfold.…”
Section: Modulation Of Gut Mao Enzymesmentioning
confidence: 99%
“…88 and 5.02, respectively. 24 A number of studies revealed the high lipophilicity of various MDR-reversal agents 25,26 ; for example, the calculated logP values of a number of 1,4-dihydropyridines which reverse MDR were in the region of 5.1-7.5. 27 The calculated logP values of the compounds in series 4-9 and verapamil are presented in Table 1 …”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…Thus groups which are lipophilic and have MR values of approximately 5-6 should be placed in the arylidene aryl rings, for example, the trifluoro-methyl substituent has π and MR values of 0.88 and 5.02, respectively. 24 A number of studies revealed the high lipophilicity of various MDR-reversal agents 25,26 ; for example, the calculated logP values of a number of 1,4-dihydropyridines which reverse MDR were in the region of 5.1-7.5. 27 The calculated logP values of the compounds in series 4-9 and verapamil are presented in Table 1 The potential of these compounds as MDR revertants will be enhanced if bioactivity is displayed at lower concentrations than 4 μg/ml and reversal of MDR occurs in a different species and another neoplastic disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation